Post-exercise Hypotension in Patients With Coronary Artery Disease - Iellamo, Ferdinando; Perrone, Marco Alfonso; Caminiti, Giuseppe; Volterrani, Maurizio; Legramante, Jacopo M. (Frontiers in Physiology, 2021)
Background: Blood pressure (BP) and hemodynamic changes occurring in the recovery phase after a single bout of exercise have not been extensively studied in coronary artery patients, despite the potential clinical implications of reducing BP through exercise. This study aimed at investigating the hemodynamic and arterial baroreflex mechanisms possibly involved in post-exercise hypotension (PEH) in patients with coronary artery disease. Methods: In 42 normotensive coronary artery patients undergone a Cardiac Rehabilitation Program, we evaluated before and after their daily exercise training session: blood pressure (BP) and heart rate (HR). In a subgroup (n = 29), daily BP profile was also evaluated by ambulatory BP monitoring. In those patients showing PEH (n = 15), we evaluated: Cardiac Output (CO), Stroke Volume (SV), total peripheral resistances (TPR), forearm (FVR) and calf (CVR) vascular resistances, and spontaneous baroreflex sensitivity (BRS). Results: After exercise TPR was significantly reduced with a similar contribution from CVR and FVR, whereas CO and SV significantly increased. BRS showed a significant reduction mainly due to a BRS decrease in response to hypertensive stimuli. Systolic BP (SBP) was significantly reduced for 12 h after the end of a single exercise session. Conclusion: These findings indicate that in coronary artery patients, the recovery phase after exercise is characterized by PEH which is mediated mainly by a generalized peripheral vasodilation and appears to influence BP behavior throughout the daily life. Finally, the cardiac component of the arterial baroreflex seems to contribute indirectly to BP reduction occurring after exercise.